RETRACTED: Perlindungan Keselamatan Dan Kesehatan Kerja (K3) Melalui Desain Sarung Tangan Untuk Operator Chainsaw - Saribu, Samintola Dolok (Wellness And Healthy Magazine, 2020)
Following a rigorous, carefully concerns and considered review of the article published in Wellness and Healthy Magazine to article entitled “Perlindungan Keselamatan Dan Kesehatan Kerja (K3) Melalui Desain Sarung Tangan Untuk Operator Chainsaw” Vol 2, No 2, pp. 369-374, August 2020, https://wellness.journalpress.id/wellness/article/view/22051This paper has been found to be in violation of the Wellness and Healthy Magazine Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in https://adoc.pub/perlindungan-keselamatan-dan-kesehatan-kerja-k3-dalam-kegiat.html and https://fdokumen.com/document/kesehatan-keselamatan-kerja-568b90e9e27c7.htmlThe document and its content has been removed from Wellness and Healthy Magazine, and reasonable effort should be made to remove all references to this article.